FNAC in the diagnosis of lymph node malignancies: A simple and sensitive tool - Anne R Wilkinson; Sadhana D Mahore; Sabiha A Maimoon (Indian Journal of Medical and Paediatric Oncology)
Context: Fine needle aspiration cytology (FNAC) of the lymph node is a simple diagnostic tool to diagnose suspected and unsuspected secondary and primary lymph node malignancy. Aim: To study the utility of FNAC in the diagnosis of clinically suspected and unsuspected lymph node malignancy. Design: A cross-sectional hospital based study on 50 patients diagnosed to have primary or secondary lymph node malignancy by cytology, and confirmed by histopathology. Materials and Methods: Lymph node aspirate smears reported as malignant were studied and the findings were correlated with histopathology. Clinical and radiological data were also noted. Statistical Analysis: The data were tabulated as per the involvement of the various lymph node groups and the types of secondary and primary lymph node malignancies involved. Results: 45 cases of metastatic malignancy and five cases of lymphomas were diagnosed by FNAC of lymph nodes. Histopathological correlation was available in all cases. Malignancy was clinically unsuspected in nine cases (18%). Conclusion: FNAC of lymph nodes is a very useful, simple and sometimes the only tool in the diagnosis of lymph node malignancies.